Improving the accuracy of real-time precipitable water vapour using country-wide meteorological model with precise point positioning in Thailand. Issue 2 (4th May 2022) - Charoenphon, Chaiyut; Satirapod, Chalermchon
ABSTRACT: Atmospheric sensing by Global Navigation Satellite System (GNSS) signals has been exclusively studied for over two decades. This study derives the real-time Precipitable Water Vapour (PWV) by taking 1 month GNSS observation data from 11 stations. A Country-wide Pressure and Temperature (CPT) model is applied to precisely determine PWV from Zenith Tropospheric Delay (ZTD). It shows that the computed ZTD RMSE obtained from most stations is less than 15 mm, meeting a threshold of 15 mm input to its Numerical Weather Prediction (NWP) equation while the average RMSE of PWV is less than 3 mm; suitable for weather nowcasting.